Resource or risk? The role of higher education parental involvement in students’ future-aware work ethic - Csók, Cintia; Lánczi, Viktória; Pallay, Katalin; Hrabéczy, Anett; Orosz, Ildikó (Central European Journal of Educational Research, 2026)
One of the key determinants of higher education students’ academic progress is future-oriented work ethic, which can be reflected in persistence in pursuing long-term goals, goal-directed effort, and disciplined work practices. The aim of this study is to examine how different patterns of parental involvement in higher education are associated with students’ future-aware work ethic and how these forms of involvement function as either resources or risk factors in its development. The analysis is based on a secondary examination of data from the 2023–2024 survey of the MTA–DE Public Education Development Research Program (N = 1,336), conducted among higher education students in Hungary and Hungarian minority regions of the Carpathian Basin. To identify patterns of parental involvement, cluster analysis was applied, followed by an examination of the relationship between the identified clusters and the studied attitude using analysis of variance and two-step linear regression models. The findings indicate that parental involvement does not exert a uniform effect on students’ future-oriented work ethic. Students with highly involved parental backgrounds are characterized by significantly higher levels of future-oriented work ethic, and this association remains robust even after controlling for socio-demographic background variables. In contrast, ambivalent parental involvement shows a consistently negative relationship with the examined attitude. The effect of low parental involvement weakens when background factors are taken into account, suggesting a mediating role of social background. Overall, the results highlight that the quality and patterns of parental involvement play a decisive role in shaping this form of work ethic: supportive and consistent parental engagement can be interpreted as a resource, whereas ambivalent involvement constitutes a risk factor.